Community-based Management of Micronutrient deficiency in Malnourished Children in Ghana (Bangladesh Journal of Medical Science, 2014)
The relationship between undernutrition and ill health is complex. It is complicated by growth retardation, impaired mental development, and significant morbidity from malaria, diarrhoeal diseases, pneumonia etc. and mortality. Several micronutrients are required for adequate growth and development especially in young children. They also account for three of the four most important forms of malnutrition worldwide. This review attempts to evaluate the community-based management of malnutrition in developing countries while comparing it to the in-patient management of malnourished children. Parameters evaluated include cost, coverage, choice, nosocomial infection acquisition and effect on productivity. The community-based management of severe malnutrition has many benefits that should be harnessed by healthcare givers so as to reduce the burden of malnutrition in low resource settings.DOI: http://dx.doi.org/10.3329/bjms.v13i4.20552Bangladesh Journal of Medical Science Vol.13(4) 2014 p.383-387